Nivel de conocimiento sobre autocuidado en el paciente con Diabetes Mellitus - Sigüenza Asmad, John Dexter (2019)
Objective: To identify the level of knowledge about self-care in patients with diabetes mellitus (DM), according to age, level of education and time of disease. Identify it in the dimensions of physical exercise, diet, foot care and pharmacological treatment. Materials and methods: Observational, descriptive and cross-sectional study. A questionnaire was applied to 206 patients with DM of Hospital Regional Docente de Trujillo in the period November-2018 to March-2019. The Chi Square test and 95% confidence intervals were used for statistical analysis. Results: 50.97% of patients had an intermediate level of knowledge about self-care. There was no significant difference of this according to age, level of education and time of disease (p>0.05). Diet was the dimension where patients knew less and there was a significant difference regarding knowledge about physical exercise, foot care and drug treatment, where a high level of knowledge was found (p <0.05). Conclusions: The level of knowledge about self-care in patients with DM is intermediate. It is not associated with the level of education, age or time of disease. The level of knowledge about physical exercise is high; about diet is intermediate; about foot care is high; and about pharmacological treatment is high.